DEVELOPMENT OF "SALIRA" INTERACTIVE VIDEO BASED ON STEAM TO ENHANCE SCIENCE AND LITERACY SKILLS IN EARLY CHILDHOOD - Ula Nur Hayatiningsih; Hanurawan, Fattah; Samawi, Ahmad; Imron Arifin; Pramono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study stemmed from the low science and literacy skills of early childhood students at TK Muslimat NU 45 Malang, attributed to the prevalence of conventional learning methods and the lack of concrete visual media. This research aims to develop "SALIRA Interactive Video" learning media based on the STEAM (Science, Technology, Engineering, Arts, Mathematics) approach and to assess its feasibility, practicality, and effectiveness. The method employed was Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this research were all 39 students at TK Muslimat NU 45 Malang. Data were collected using expert validation sheets, practicality response questionnaires, and learning outcome tests. Validation results indicated that the product falls into the "Very Feasible" category with an average score of 90.75%. The practicality test yielded a score of 94.0%, categorized as "Very Practical." The effectiveness test results demonstrated a significant increase in the average science ability score from 54.5 to 86.0, and literacy ability from 56.0 to 88.5. It is concluded that the STEAM-based SALIRA Interactive Video is feasible and effective for enhancing early childhood science and literacy skills.